Kepemimpinan Rasulullah di Bidang Pendidikan (Studi Literatur) - Oktavia, Lidya Fransiska; Yovica, Alia; Asmendri, Asmendri; Sari, Milya (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article aims to understand the leadership of the Prophet Muhammad (peace be upon him) in the field of education. This research uses a qualitative approach with a literature study method. Data was collected through documentation techniques, namely by identifying, reading, and recording information from written sources. Subsequently, the data was analyzed descriptively and qualitatively. The analysis was conducted thematically with an emphasis on the principles of educational leadership exemplified by the Prophet Muhammad (peace be upon him), such as setting an example, communication, motivation, character building, and a personal approach to students. The validity of the data is maintained through source triangulation and consistency of interpretation against the literature used. The results of the analysis show that the Prophet Muhammad (peace be upon him) is an exemplary leader who played an important role in establishing the Islamic education system since the early days of Islam. His leadership in the field of education demonstrates a significant concern for the dissemination of knowledge, the development of morals, and the empowerment of the community. The Prophet Muhammad (peace be upon him) not only taught knowledge but also provided real examples in daily life. He made education the main means to form a pious, knowledgeable, and moral society. His democratic, compassionate, yet firm leadership style serves as an ideal model for educational leadership today.